Disability Sports as a Psychological Well-Being Intervention Tool for Persons with Disabilities - Dyah Permatasari; Mayang Ayu Angelita Sari; Reza Asep Adi Purnomo (International Conference on Psychology and Education (ICPE), 2023)
The purpose of this study was to find out the role of disability sports on the psychological well-being of persons with disabilities. The research method uses a literature review by searching the selected keywords, namely "Disability Sports", "Psychological Well-being", and "Self-esteem". From the research that has been done, it can be concluded that sports with disabilities can improve and maintain physical and mental health, with physical and mental development, self-esteem will increase. Disability sports also motivate people with disabilities to be able to actualize themselves in all existing limitations so that psychological well-being can be achieved.